ESPECIFICAÇÕES E VERIFICAÇÃO GEOMÉTRICA EM UM AMBIENTE DE PLANEJAMENTO AVANÇADO DA QUALIDADE DO PRODUTO - Ribeiro, Luis F. M.; Eckhardt, Moacir; Heimburg, Julio C. V.; Benini, Lucas; Ferreira, Thiago A. (Salão do Conhecimento, 2013)
Resumo